Vascular Endothelial Growth Factor Receptor Inhibitors in Chinese Patients With Advanced Radioactive Iodine-Refractory Differentiated Thyroid Cancer: A Network Meta-Analysis and Cost-Effectiveness Analysis - Zhu, Youwen; Liu, Kun; Wang, Kailing; Peng, Libo (Frontiers in Endocrinology, 2022)
Introduction: Two targeted drugs (apatinib and lenvatinib) show clinical efficacy in first-line treatment of Chinese patients with radioactive advanced iodine-refractory differentiated thyroid cancer (RAIR-DTC) and are recommended by the Chinese Society of Clinical Oncology guidelines. Considering the high clinical cost of long-term vascular endothelial growth factor receptor inhibitor administration and to determine which of the two targeted drugs is preferable, we opted to conduct a cost-effectiveness analysis (CEA) and network meta-analysis (NMA). Material and Methods: The results of NMA and CEA included in the two phase III randomized clinical trials REALITY (NCT03048877) and Study-308 (NCT02966093), in which Bayesian NMA and CEA were performed on 243 and 149 Chinese patients, respectively, were retrieved. Overall survival and progression-free survival (PFS) for apatinib versus lenvatinib were determined by NMA. CEA involved the development of a 20-year Markov model to obtain the total cost and quality-adjusted life-years (QALYs), and this was followed by sensitivity and subgroup analyses. Results: Compared with lenvatinib, apatinib therapy provided a 0.837 improvement in QALY and 6,975 reduction in costs. The hazard ratio of apatinib versus lenvatinib and the cost of the targeted drugs had a significant impact on the model. According to the sensitivity analysis, apatinib was more cost-effective and had no correlation with willingness-to-pay in China. Subgroup analysis showed that apatinib maintained PFS more economically. Conclusion: NMA and CEA demonstrated that apatinib was more cost-effective compared to lenvatinib in the first-line treatment of Chinese RAIR-DTC patients.